Undergraduate teaching and assessment needs in ethics and professionalism on clinical ward rounds involving medical students, Faculty of Health Sciences, Stellenbosch University (SU) : a nonexperimental descriptive study. - Heyns, Louis (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--Stellenbosch University, 2011.